INNOVATIVE APPROACHES TO ENSURING OCCUPATIONAL HEALTH AND SAFETY: CHALLENGES AND OPPORTUNITIES - Trus, O.; Berezovskyi, A.; Prokopenko, E. (Municipal economy of cities. Series: «Economy science», 2024)
Today, developing and implementing an efficient occupational health and safety system is an essential component of the management paradigm that ensures the preservation of personnel life, health, and working capacity in performing their work duties. Innovative activities in this area synergise modern information solutions to improve personnel training methods and introduce analytical control, technological monitoring systems, and a range of the latest digitalised personal protective equipment. The article analyses innovative approaches and technologies in occupational health and safety. It establishes that the occupational health and safety management system cannot be static. It must constantly adapt to changes in the production environment and the legislative field, which requires prompt response to new challenges and forecasting possible scenarios of variability in working conditions. The study examines the current capabilities of innovative approaches to occupational safety and the potential of the latest technological solutions to improve the occupational health and safety system. The study identifies related challenges and issues and ways to mitigate them. It proves that modern innovative technologies and tools of the occupational safety system rely on attracting new approaches to analysing informative data on the risks of accidents and injuries at work, with the further development of preventive measures to minimise production hazards. Innovative solutions for the occupational health and safety concept include a management paradigm aimed at improving the employee training system using training and computer technologies, implementing systems for effective analytical control over technological processes, and providing personnel with tracking devices and the latest digitalised personal protective equipment. The authors have identified priority preventive measures, among which are promising technologies for teaching safe labour practices and improving safety culture in general. The practical significance of the research results is in the possibility of their application in modern production conditions to strengthen existing safety approaches.